FSO system performance analysis based on novel Gamma–Chi-square irradiance PDF model - Todorović, Jelena; Spalević, Petar; Panić, Stefan; Milosavljević, Bojana; Gligorijević, Milan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
In order to provide a novel analytically traceable free space optics (FSO) channel model for describing turbulence based irradiance fluctuations, following basic scintillation theory principles, we have derived closed-form expression for probability density function (PDF) of a new statistical Gamma–Chi-square model. Further, capitalizing on provided model, error performances of FSO system over on–off keying (OOK) transmission scheme both in the presence of atmospheric turbulence and misalignment fading (pointing error) is investigated. For both cases, the average bit error rate (ABER) at the receiving side of the system is determined in an analytically closed form. The results are graphically presented in order to analyze the impact of different levels of turbulence, as well as other relevant parameters, on the quality of the received signal in the OOK modulated FSO system.
Optica Applicata, Vol. 51, 2021, nr 3, s. 335-348
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; free space optical (FSO); Gamma–Chi-square distribution; atmospheric turbulence; pointing error; on–off keying (OOK)